La constitucionalización de la formación política y su vinculación con el derecho a la educación - Ríos Rengifo, Alex Junior (2024)
Political education is closely related to the right to education, a fundamental right recognized internationally, which must be understood from a broad perspective to avoid any type of limitation or discrimination. Therefore, it is essential to promote its dissemination in academic and legal fields. The constant transformations that our society has undergone have encouraged the analysis of educational evolution and the inclusion of new knowledge, such as politics, in educational centers. However, prejudices persist regarding its teaching, which makes its express recognition in the legal system difficult, despite the universal approach to education. For this reason, the main objective of this study is to establish legal foundations that support its recognition in the Constitution and highlight its connection with the right to education.